Effect of strain-dependent dynamic properties of backfill and foundation soil on the external stability of geosynthetic reinforced waterfront retaining structure subjected to harmonic motion. (October 2019) - Annapareddy, VS Ramakrishna; Pain, Anindya
Abstract: A simplified method to determine the minimum length of reinforcement required for the external stability of waterfront reinforced soil structures under seismic conditions is presented. In the present analysis, strain-dependent dynamic properties (shear modulus and damping ratio) are used. The results obtained from the present method are well compared with the results of pseudo-static method of analysis. For the set of input parameters, the estimated minimum length of reinforcement required against sliding failure is nearly 27–29% higher for an input normalized frequency of 1.06 and is nearly 22–25% lower for another input normalized frequency of 1.94 when compared with the results of pseudo-static approach. This can be attributed to the mode change behaviour of the waterfront structure. In addition, the effect of foundation type on the external stability of waterfront reinforced soil structures has also been presented and it is found that the foundation type has a significant effect on the same. For the given set of input parameters, the length of minimum reinforcement required for a slope and vertical wall having a flexible foundation are about 26–28% and 32–38% larger than that of a slope and vertical wall with rigid foundation, respectively.